Topology of the electron density in open-shell systems - Lobayan, Rosana Maria (2010)
This work describes the decomposition of the electron density field of open-shell molecular systems into physically meaningful contributions. The new features that the open-shell nature of the wave function introduces into these fields are topologically studied and discussed, showing the charge concentration and depletion regions within the system. The localized character (field concentration only close to the nuclear positions of the system) or the nonlocalized character (concentration in other regions of the system) is used to study the reliability of the Lewis model of bonding to describe chemical bonding phenomenon in open-shell systems. Numerical examples are reported for molecular systems at a correlated level of approximation, in the single-double configuration interaction wave function approach. © 2010 American Chemical Society.